Body composition and risk of liver cancer: a population-based prospective cohort study on gender difference - Pi, Sainan; Liu, Anran; Zhu, Beibei; Zhu, Yunxiao; Yuan, Jinqiu; Zhang, Zheming; Gao, Chang; Fu, Jinxian; Liu, Yao; Liang, Xujing; Xia, Bin; Chen, Youpeng (Frontiers in Nutrition, 2023)
Background: Obesity is a common and highly convincing risk factor for many cancers, including liver cancer. Sex disparities in body composition and the regulatory mechanisms involved in energy homeostasis may contribute to difference in the incidence of cancer. However, evidence on gender-specific association between body composition and liver cancer incidence is limited. We performed this study to investigate the linear and non-linear associations of body composition with liver cancer risk by gender. Materials and methods: This prospective analysis included 475,659 participants free of cancer based on the UK Biobank. We used Cox proportional hazard models to calculate the hazard rations (HRs) and 95% confidence intervals (CIs) after adjusting for potential confounders. Restricted cubic spline was performed to investigate the potential nonlinear associations. Results: During a median follow-up, 275 cases (174 males and 101 females) of liver cancer were identified. Males in the highest body fat percentage group is more likely to develop liver cancer (HR= 1.89, 95% CI: 1.17-3.03) compared with those in the lowest group. One unit increased of whole-body fat mass, arm fat mass, trunk fat mass was associated with 1.03-, 1.14- and 1.05-fold increased risk of liver cancer in male, respectively. U-shaped associations of body composition with liver cancer risk were observed in the female. Both high and low level of whole-body fat-free mass, particularly in arm and trunk, were associated with an increased risk of liver cancer. Conclusion: The study found a gender-specific association between body composition and liver cancer risk and provided evidence for individualized weight management for the prevention of liver cancer.